cAMP increases junctional conductance and stimulates phosphorylation of the 27-kDa principal gap junction polypeptide. - Saez, J C (1986)
Membrane-permeant cAMP derivatives (dibutyryl- and 8-bromo-cAMP) increase gap-junctional conductance within minutes when applied to voltage-clamped pairs of rat hepatocytes. Glucagon also increases junctional conductances, but the response has a more rapid onset and is more rapidly reversible. The glucagon effect can be prevented by intracellular injection of the protein inhibitor of the cAMP-dependent protein kinase (Walsh inhibitor), indicating that the catalytic subunit of cAMP-dependent protein kinase is directly involved. The 27-kDa major gap junction polypeptide is phosphorylated when liver cells dissociated into small groups are incubated with 32P. Addition of 8-bromo-cAMP to cells increases the incorporation of 32P into the 27-kDa junctional protein. Serine is the amino acid residue that is phosphorylated. When isolated liver gap junctions are incubated in the presence of catalytic subunit of the cAMP-dependent protein kinase, the 27-kDa gap junction polypeptide is phosphorylated with low stoichiometry on serine. The rapid increases in gap junctional conductance caused by agents that elevate cAMP and phosphorylation of the gap junction protein by cAMP-dependent protein kinase suggest that cAMP-dependent phosphorylation of the gap junction channel modulates the conductance of liver gap junctions.